BENTUK PEMBERDAYAAN WANITA KARIER DALAM PERSPEKTIF AL-QUR’AN DAN HADIST - Nursyaidah, Nursyaidah (IAIN Padangsidimpuan, 2019)
The concept of community empowerment when examined actually departs from a view which is placed human as subjects from their own world. The basic pattern of the empowerment movement mandates the need for power and emphasizes alignments with powerless groups. The way in which empowerment is done is by providing motivation or support in the form of providing resources, opportunities, knowledge, and skills for the community to increase their capacity, raising awareness about their potential, then striving to develop their potential. Women need to be given training, education, and even empowerment, so that they have the ability to live properly and can help their husbands to meet their daily needs. The goal is that women have the ability / expertise.In the context of women workers, she is welcome to choose the field or sector that she likes which is certainly in accordance with the capabilities and professionalism possessed. According to Islamic teachings, whatever role is held by women, especially as housewives should not be forgotten, so that the possibilities of negative access can be avoided. So, serious attention from women to foster their families is very necessary because the task is the most important of the efforts to develop the community widely. Upright and the collapse of a country's society is very close which is related to the state of totality of family units forming a country's society. Islam allowed women to work outside the home while women can place themselves based on their female nature.